Simulation and dynamic model of the control process of the lighting system of industrial premises of large areas. Issue 3 (November 2020) - Kukartseva, O I; Tynchenko, V S; Antamoshkina, O I; Markevich, E A; Pilipenko, A E; Leonteva, A A
Abstract: The article presents a simulation-dynamic model of the control process of the lighting system of industrial premises of large areas. The model is based on the system dynamics method, which is widely used in many areas. The presented model of the lighting system includes three levels, two streams, and other variables that are used in the process of its operation. The input interface allows you to enter data into the model using the PowerSim Studio program. This work consists of several elements: the model itself and three graphs that show the results of three experiments with different input data. The results are presented in a table with output data, which is reflected in the program in the output interface and indicates that with a large number of lamps and with the highest values of possible breakdowns, the number of lamps that will stop burning increases. The model is designed for operational management of the system and ensuring appropriate lighting of premises, as well as maintaining inventory and the desired quality of lighting of production premises of large areas.